Advances in Foxp3+ regulatory T cells (Foxp3+ Treg) and key factors in digestive malignancies - Wang, Wanyao; Ding, Minglu; Wang, Qiuhong; Song, Yidan; Huo, Keyuan; Chen, Xiaojie; Xiang, Zihan; Liu, Lantao (Frontiers in Immunology, 2024)
Foxp3+ regulatory T cells (Foxp3+ Treg) play a role in regulating various types of tumors, but uncertainty still exists regarding the exact mechanism underlying Foxp3+ Treg activation in gastrointestinal malignancies. As of now, research has shown that Foxp3+ Treg expression, altered glucose metabolism, or a hypoxic tumor microenvironment all affect Foxp3+ Treg function in the bodies of tumor patients. Furthermore, it has been demonstrated that post-translational modifications are essential for mature Foxp3 to function properly. Additionally, a considerable number of non-coding RNAs (ncRNAs) have been implicated in the activation of the Foxp3 signaling pathway. These mechanisms regulating Foxp3 may one day serve as potential therapeutic targets for gastrointestinal malignancies. This review primarily focuses on the properties and capabilities of Foxp3 and Foxp3+Treg. It emphasizes the advancement of research on the regulatory mechanisms of Foxp3 in different malignant tumors of the digestive system, providing new insights for the exploration of anticancer treatments.